Implementation of Nutrition Education and High-Calcium Supplementary Feeding Demonstration in Stunting Prevention: Knowledge Level and Satisfaction of Mothers with Toddlers - Yanuarti Petrika; Suaebah; Widyana Lakshmi Puspita; Sri Rezki; Pawarti; Neny Setiawaty N; Asmadi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Stunting is a critical global health issue, with Indonesia experiencing high prevalence rates, particularly in regions like West Kalimantan, where the rate reached 26.6% in 2018. Despite some progress in reducing stunting rates, urgent interventions are necessary, particularly through government initiatives focused on improving nutritional status among pregnant women and young children, as well as comprehensive nutritional education programs to raise awareness and promote healthier dietary practices. The purpose of this community service activity is to enhance the knowledge of mothers with toddlers and improve their dietary intake, particularly focusing on foods rich in calcium to support the physical growth of children. The study utilized a quantitative approach with a quasi-experimental design, specifically a pretest-posttest format without a control group, to assess the impact of educational interventions on mothers' knowledge of stunting and calcium-rich foods. Participants included 25 mothers of toddlers from Posyandu Berdikari, who were engaged through interactive lectures and cooking demonstrations over two months. Knowledge was measured using pretest and posttest questionnaires, while satisfaction with food products was evaluated through a 5-point Likert scale. Data analysis included the Wilcoxon Rank Test for knowledge changes and descriptive statistics to assess satisfaction and organoleptic preferences. The community service program resulted in a significant increase in knowledge among 19 out of 25 respondents, with an average improvement of 25 points and statistical significance (P = 0.00). Additionally, 80% of participants expressed high satisfaction with the calcium-rich Nugget products, while 96% of mothers felt prepared to practice the PMT recipes at home. This indicates a positive impact on both knowledge and acceptance of nutritional education and products. The nutrition education program significantly improved mothers' knowledge about stunting, leading to high satisfaction with calcium-rich products and readiness to implement PMT recipes at home.